Application of Contextual Strategy with Audio Visual Media to Increase Interest in Learning Indonesian Language in Students - Zebua, Yogi Chris James; Waruwu, Agus Zan; Bawamenewi, Arozatulo; Gea, Theresia Jeni Kristina (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia, 2024)
In learning Indonesian, the study of practical problems regarding language in everyday life is very useful for a child or student in living and living now and in the future. With the hope that these students will later be able to realize and understand that they cannot live without the contribution of language in every action, but living in a large environment is very difficult when the language used is not appropriate to the context, if you want to live a decent life then language is one of the tools to be able to connect good communication with others. The next problem is related to the choice and learning approach, which has not generated much student activity and creativity. This is because they still often use conventional approaches, where learning is centered on the teacher, so that students become passive. If the learning can activate students, it will be interesting and the large amount of material can be quickly absorbed by students. Because they are enthusiastic, want to learn seriously. Based on the problem above, we are interested in implementing a contextual learning model which is seen as being able to help students be active in learning and teaching activities. The aim of this research is to find out the influence of contextual learning on increasing students' interest in learning Indonesian. To find out whether there is an increase in students' interest in learning Indonesian. To determine the simultaneous influence of contextual learning and student interest in learning on the learning achievement of class IX students at SMP Negeri 3 Bawolato. The method used in this research is a quantitative method by applying an experimental approach to class IX students at SMP Negeri 3 Bawolato, data collection using research instruments, (1) attention to learning, (2) participation in learning activities, (3) effort in completing assignments, (4) interest in learning material. The results of the research show that there is a simultaneous influence of contextual learning and student interest in learning on the learning achievement of class IX students at SMP Negeri 3 Bawolato. Students' perceptions of the contextual learning model have a greater effective contribution to increasing students' interest in learning Indonesian, although not yet to its full potential.